Reception of Tāj al-Dīn al-Subkī’s Jamʿ al-Jawāmiʿ and Its Impact on Post-Classical Uṣūl al-Fiqh Literature - al-Hudawi, Mohamed Jabir Ali (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objective: This study examines post-classical uṣūl al-fiqh literature through Tāj al-Dīn al-Subkī's (d. 771/1370) seminal work Jamʿ al-jawāmiʿ. The inquiry investigates factors contributing to this text's establishment as an educational cornerstone and its impact on Islamic legal scholarship across juristic traditions. Research Method: The research employed historical analysis of biobibliographical sources, tracing commentary evolution across juristic schools. This approach facilitated the reconstruction of intellectual networks through which Jamʿ al-jawāmiʿ proliferated beyond its 8th/14th-century Shāfiʿī origins. Results: This treatise rapidly transcended temporal and geographic boundaries to become integral to Islamic legal education worldwide. The text catalyzed a substantial commentary corpus from diverse juristic schools, demonstrating exceptional scholarly reception across traditional boundaries. Findings and Implications: Analysis reveals sophisticated interplay between base text (matn) and commentary literature, challenging reductive assumptions regarding post-classical Islamic scholarship's originality. Textual transmission practices constituted dynamic sites of intellectual engagement rather than knowledge preservation. Conclusion: Jamʿ al-jawāmiʿ established itself as a pivotal node in uṣūl al-fiqh development, with enduring influence manifested through successive generations of scholarly engagement, transcending juristic schools. Contribution: This study reconceptualizes Islamic legal knowledge transmission, highlighting the commentary literature's critical role in intellectual innovation within traditional educational frameworks. Limitations and Suggestions: Despite source accessibility constraints, the research illuminates underappreciated dimensions of Islamic scholarly traditions. Future scholarship would benefit from a deeper investigation into interpretive legacies within evolving contexts.